Tinjauan Prinsip Akuntabilitas Syariah dan Permendagri No. 13 Tahun 2014 pada Pengelolaan Dana Desa: (Studi pada Desa Ringinpitu Kabupaten Tulungagung) - Putri, Erika Indah Sastiya (Al-Muhasib: Journal of Islamic Accounting and Finance, 2023)
This study aims to determine the role of the village government in managing village funds from the perspective of Sharia Accountability Principles and Minister of Home Affairs Regulations No. 13 of 2014 in Ringinpitu Village, Tulungagung Regency. The study focuses on planning, implementation, administration, accountability, and reporting while adhering to the relevant rules. Additionally, the research aims to determine how the government can fulfill the needs of the local community while following Islamic law. This research is classified as qualitative research that is based on interviews and observations. The informants in this study are the members of the village government who play a crucial role in managing village funds.  The results of this study indicated that the village government played a significant role in managing the funds according to Islamic Law, which benefited the community. The government conducted open deliberations and provided evidence of reporting activities, which were accompanied by the treasurer and approved by the village head.